2009
DOI: 10.1111/j.1468-2435.2008.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual versus Household Migration Decision Rules: Gender and Marital Status Differences in Intentions to Migrate in South Africa

Abstract: This research tests the thesis that the neoclassical microeconomic and the new household economic theoretical assumptions on migration decisionmaking rules are segmented by gender, marital status, and time frame of intention to migrate. Comparative tests of both theories within the same study design are relatively rare. Utilizing data from the Causes of Migration in South Africa national migration survey, we analyse how individually held ''own-future'' versus alternative ''household well-being'' migration deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 25 publications
4
52
1
1
Order By: Relevance
“…This suggests a shift from migration historically being dominated by unmarried men, when the girls' place was at home. It also agrees with the findings by Gubhaju and De Jong (2005) that households in Thailand trust never married females in remittance sending and they encourage them to migrate more than males. Therefore, it seems as if females are no longer confined to the domestic arena and they are active participants in seeking incomes for Zimbabwean households.…”
Section: The Migration Decisionsupporting
confidence: 91%
“…This suggests a shift from migration historically being dominated by unmarried men, when the girls' place was at home. It also agrees with the findings by Gubhaju and De Jong (2005) that households in Thailand trust never married females in remittance sending and they encourage them to migrate more than males. Therefore, it seems as if females are no longer confined to the domestic arena and they are active participants in seeking incomes for Zimbabwean households.…”
Section: The Migration Decisionsupporting
confidence: 91%
“…Key personal characteristics which influence decisions to move include age, sex, educational level, wealth, marital status, attachment to place, and attitudes and preferences (such as degree of risk aversion). Decisions are frequently made in a family context, so the characteristics of the family unit, and power relationships within it, are also important; the relative effects of personal and household characteristics vary between members of a community (Gubhaju and de Jong, 2009). Barriers or obstacles to movement include the cost of moving, access to the means of moving, and the presence of legal or administrative barriers and constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that household theories of migration consider a household to be composed of actors with equal power and agreed aims, though this is quite often not the case, especially in cultures where women have less power than men in the family decisionmaking (de Haas & Fokkema, 2010;Gubhaju & De Jong, 2009;Hoang, 2011;Stecklov, Carletto, Azzarri, & Davis, 2010).…”
Section: Social Context In Migrationmentioning
confidence: 99%
“…In addition, research has also shown that partners can have differing goals in the migration process (Gubhaju & De Jong, 2009;Pedraza, 1991) and that consensus building is often done through discussion (Adams, 2004;De Jong, Warland, & Root, 1998). Not only are couples involved in the decision, but also others, such as extended family, children and friends, can have influence in the decision-making process (Adams, 2004).…”
Section: Social Context In Migrationmentioning
confidence: 99%
See 1 more Smart Citation